Migration to PaaS clouds - Migration process and architectural concerns - Pahl, Claus; Huanhuan Xiong (2013 IEEE 7th International Symposium on the Maintenance and Evolution of Service-Oriented and Cloud-Based Systems, 2013)
In the cloud computing technology stack, infrastructure has matured more than platform or software service technologies with respect to languages and techniques used for architecting and managing respective applications. Platform-as-a-Service (PaaS) emerges as a focus for the near future that we will focus on. We look at software architecture and programming concerns in the context of migration to PaaS solutions, i.e. the transition of platform systems from on-premise to cloud solutions. We investigate best-practice approaches in cloud-aware coding in the form of patterns and formulate these as a migration process. While one-to-one mappings of software from on-premise to cloud platforms are possible, statelessness and data externalisation from stateful sessions and applications emerge as solutions if cloud benefits such as elasticity and performance are aimed at.